Deep Learning Manifestation for TEYL at PPA IO-0133 Krammer Hilina’a Kota Gunungsitoli - Telaumbanua, Yasminar Amaerita; Zebua, Meniati; Gulo, Dari Hati; Waruwu, Pujawati; Waruwu, Yaredi; Zebua, Hasna; Halawa, Zun Kelvin Eferistus Albers (PT Media Edukasi Nusantara, 2026)
This community service program aims to describe the manifestation of deep learning principles—joyful, meaningful, and mindful learning—in teaching English for young learners in a non-formal education setting. The program was conducted at a Pusat Pengembangan Anak (PPA) involving learners aged 9–11 years and implemented over seven instructional meetings. A descriptive qualitative approach was employed, with data collected through field notes and observation sheets. The findings show that joyful learning was manifested through students’ enthusiasm, active participation, and positive emotional engagement during learning activities. Meaningful learning appeared as students connected English materials with their daily experiences and used language in relevant contexts. Mindful learning was reflected in students’ attention, cooperation, and gradual awareness of the learning process. These findings indicate that deep learning principles can be effectively implemented in non-formal English learning contexts and highlight the potential of community-based programs in supporting meaningful and sustainable English education for young learners.